PERAN POLA ASUH ORANG TUA TERHADAP KEMANDIRIAN ANAK KELOMPOK B DI RAUDHATUL ATHFAL AT TIBYAN KOTA MALANG - Faridah Faridah; Muhammad Hanif; Ika Anggraheni (UNISMA, 2020)
The main problem in this research is the low independence of children in Raudhatul athfal AT TIBYAN Malang City. This research is a qualitative approach using descriptive methods. Parenting is the attitude of parents in their relationship with their children. This attitude can be seen from various aspects, including from the way people provide arrangements to children, parents, educate, and discipline in achieving the process. maturity both directly and indirectly. Instilling independence in children is very important, independence is the most basic education in the process of child growth and development. Parenting style is very helpful in the development and maturity of children in the developmental stage of children's learning. Children who have a sense of independence will be able to adapt to their environment. And overcome the difficulties they face themselves.